2012
DOI: 10.5897/ajb11.2004
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation effects on the composition of blood in Nubian ibex (Capra nubiana) in Saudi Arabia

Abstract: The aim of this study was to investigate the effect of seasonal variation on the haematological and biochemical parameters in adult captive wild male Nubian ibex (Capra nubiana), a group of 20 Nubian ibex was selected for the study. Haemoglobin (Hb), glucose concentration (Glu), blood urea nitrogen (BUN), total proteins (TP), albumin (Alb), globulin (Glob), calcium (Ca), magnesium (Mg) and phosphorous (P) were studied. However, haemoglobin, glucose concentration, total plasma protein were higher during summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…However, serum globulin (Glb) concentration increased (p<0.05) in shorn ewes compared with unshorn ewes during spring, reflecting a decrease in albumin to globulin ratio in the same season. Al-Eissa et al (2012) observed higher Glb concentration in Nubian goats under cold climatic conditions that led to decreased Alb: Glb ratio. In this line, Ribeiro et al (2018) reported that differences in globulin values are related to physiological and genetic factors of animal adaptation.…”
Section: Blood Biochemical Parametersmentioning
confidence: 77%
“…However, serum globulin (Glb) concentration increased (p<0.05) in shorn ewes compared with unshorn ewes during spring, reflecting a decrease in albumin to globulin ratio in the same season. Al-Eissa et al (2012) observed higher Glb concentration in Nubian goats under cold climatic conditions that led to decreased Alb: Glb ratio. In this line, Ribeiro et al (2018) reported that differences in globulin values are related to physiological and genetic factors of animal adaptation.…”
Section: Blood Biochemical Parametersmentioning
confidence: 77%
“…Differences in the globulin values are related to physiological and genetic factors of animal adaptation. Abdelatif et al (2009) andAl-Eissa et al (2012) observed higher levels of globulin in the rainy period, resulting in a low ALB/globulin ratio.…”
Section: Resultsmentioning
confidence: 95%
“…Animals respond differently to drastic temperature changes by altering several aspects of their physiology and behaviour Ribeiro et al 2016). These changes include alterations in physiological parameters (rectal temperature, RT; heart rate, HR; respiratory rate, RR; surface temperature, ST) (Marai et al 2007), the erythrogram (Al-Eissa et al 2012), blood biochemical parameters (Abdelatif et al 2009;Ribeiro et al 2016), and cortisol and thyroid hormones (Helal et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical and hematological variables of blood are generally used to monitor and evaluate health, nutritional and physiological status of ruminants (Chapple et al, 1991;Al-Eissa et al, 2012;Gupta et al, 2007). The evaluation of blood constituents has been widely used as a marker to determine the efficacy of feed nutrient content and supplements (Belewu and Ogunsola, 2010;Belewu et al, 2009;Akingbade et al, 2002) but also an index of transportation stress (Ambore et al, 2009).…”
Section: Introductionmentioning
confidence: 99%